2006
DOI: 10.1159/000094727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Serotonin Type 2A, 3A and 3B Receptor and the Serotonin Transporter Genes on Paroxetine and Fluvoxamine Efficacy and Adverse Drug Reactions in Depressed Japanese Patients

Abstract: In this study, we tested the influence of the serotonin type 2A, 3A and 3B receptor genes (HTR2A, HTR3A, HTR3B) in addition to a polymorphism in the promoter region of the serotonin transporter (SERTPR), and investigated the different characteristics of clinical responses to paroxetine and fluvoxamine. A total of 100 Japanese patients affected by major recurrent depression were enrolled in a randomized 6-week study. The clinical response was evaluated using the Hamilton Rating Scale for Depression (HAM-D), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 100 publications
(71 reference statements)
4
83
3
3
Order By: Relevance
“…Considering the importance of the serotonergic system in depression and for the medical treatment of it, this link between a variant serotonin receptor with pronounced augmented signaling characteristics and depression is highly interesting. In a previous study (23), a polymorphism in the regulatory region of HTR3A shown to increase gene expression (24) was found to affect the improvement observed in depressed patients upon paroxetine treatment. In addition, other studies have suggested a link between 5-HT 3 receptor activation and the treatment/ etiology of depression (5,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 90%
“…Considering the importance of the serotonergic system in depression and for the medical treatment of it, this link between a variant serotonin receptor with pronounced augmented signaling characteristics and depression is highly interesting. In a previous study (23), a polymorphism in the regulatory region of HTR3A shown to increase gene expression (24) was found to affect the improvement observed in depressed patients upon paroxetine treatment. In addition, other studies have suggested a link between 5-HT 3 receptor activation and the treatment/ etiology of depression (5,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 90%
“…Although not covering the locus systematically, several previous studies have provided suggestive evidence for an involvement of other HTR2A variants in antidepressant outcome (Minov et al, 2001;Cusin et al, 2002;Peters et al, 2004;Choi et al, 2005;Hong et al, 2006;Kato et al, 2006;McMahon et al, 2006;Paddock et al, 2007;Perlis et al, 2009). Post-mortem (McKeith et al, 1987Lopez-Figueroa et al, 2004) and positron emission tomography (PET) (Yates et al, 1990;Yatham et al, 2000;Mintun et al, 2004) studies have reported both increased and decreased HTR2A receptor number and binding in different brain regions of depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was examined in studies where genotype frequencies were included. 9,[15][16][17][18][19][20][21][22][23][24][25] Given the lack of unequivocal data for 5-HTTLPR genotype pooling, we tested both dominant and recessive hypotheses: l/l versus l/s-s/s and l/l-l/s versus s/s. Outcome was defined with three phenotypes: remission rate, response rate, and response rate within 4 weeks.…”
Section: Methodsmentioning
confidence: 99%